Revision Surgery for Failed Polyvinyl Alcohol Hydrogel Implant in the First MTP Joint: A Case Report and Comprehensive Review - Thelma R. Jimenez Mosquea MD; Christopher A. Colasanti MD; Hugo A. Ubillus MD; Raymond J. Walls MD, FRCS(Tr&Orth), MFSEM, FAAOS (Foot & Ankle Orthopaedics)
Background: Hallux rigidus is a degenerative condition of the first metatarsophalangeal (MTP) joint that can significantly impair function and quality of life. The introduction of polyvinyl alcohol (PVA) hydrogel implants, such as Cartiva, offered an alternative to arthrodesis by preserving joint motion. However, failures of these implants, often resulting in bone loss and joint instability, present a challenge for revision surgery. Methods: We report the case of a 43-year-old woman with persistent pain and functional limitations after a failed PVA hydrogel implant in the first MTP joint. The revision surgery involved a biologic resurfacing using the Osteochondral Autograft Transfer System (OATS) with a graft harvested from the ipsilateral femoral condyle, complemented by interpositional arthroplasty with a dermal graft and a proximal phalanx closing wedge osteotomy to correct residual hallux valgus. Results: At the 3-year follow-up, the patient-reported complete resolution of pain and returned to full activity with improved range of motion (40 degrees dorsiflexion, 15 degrees plantarflexion). Radiographic evaluation demonstrated graft incorporation and restoration of joint space, confirming the success of the procedure. Conclusion: This case highlights the potential of OATS combined with interpositional arthroplasty as a viable option for revision surgery in complex cases of failed synthetic cartilage implants in hallux rigidus. By addressing bone loss and preserving joint function, this approach provides a patient-specific alternative to traditional arthrodesis. Further studies are warranted to establish the long-term efficacy of this technique in similar cases. Level of Evidence: Level V, case report.